Gender Differences in Wages and Job Turnover Among Continuously Employed Workers - Light, Audrey; Ureta, Manuelita (American Economic Review, 2016)
The purpose of this paper is to determine whether a significant number of [U.S.] women work continuously during their early careers which women are likely to do so and how these women compare to men in terms of their interfirm mobility and earnings. The data are from the young men and young women cohorts of the National Longitudinal Surveys of Labor Market Experience (NLS)....Continuous employment is by no means the norm among young women but it appears to be a growing trend....In comparing starting wages of men and women we find that the wage gap is less pronounced among continuously employed workers than among the full sample in almost every race-cohort-schooling group and the gap is narrowing far more rapidly among the continuously employed. (EXCERPT)